Enhancing Islamic Education Learning Outcomes through Snowball Throwing Assisted by Smart Box Media in Elementary Schools - Yuliani; Muh. Agil Amin; Nur Fakhrunnisaa; Sumardin Raupu (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2026)
This study aims to improve students’ learning outcomes in Islamic Religious Education and Character Education through the implementation of the Snowball Throwing learning model assisted by Smart Box media at the elementary school level. The study also seeks to describe the implementation process of interactive cooperative learning and analyze its impact on students’ classroom participation, motivation, and academic achievement. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting of two cycles involving planning, acting, observing, and reflecting stages. The study was conducted at SDN 434 Kalimbubu, Kabupaten Luwu, with 12 fourth-grade students as research participants. Data were collected through observation, learning achievement tests, and documentation, and analyzed using descriptive quantitative techniques based on average scores and classical learning mastery percentages. The findings revealed that the implementation of the Snowball Throwing learning model assisted by Smart Box media significantly improved students’ participation and learning outcomes. Teacher activity implementation increased from 57.14% in Cycle I to 94.64% in Cycle II, while student learning activity improved from 35.41% to 89.58%. Students’ average learning achievement score increased from 71 in Cycle I to 83 in Cycle II, with classical learning mastery improving from 41% to 91%. The findings indicate that interactive cooperative learning supported by Smart Box media successfully created a more active, collaborative, enjoyable, and student-centered learning environment. The novelty of this study lies in the integration of the Snowball Throwing cooperative learning model with Smart Box interactive media in Islamic Religious Education learning at the elementary school level. This study contributes theoretically to the development of innovative instructional strategies in Islamic education and practically provides teachers with an effective alternative learning model to enhance students’ participation, motivation, collaboration, and academic achievement.